Early neurocognitive improvements following parathyroidectomy for primary hyperparathyroidism. (16th May 2017) - Shah‐Becker, Shivani; Derr, Jonathan; Oberman, Benjamin S.; Baker, Aaron; Saunders, Brian; Carr, Michele M.; Goldenberg, David
Abstract : Objectives: To establish a time frame for postoperative improvements in neurocognitive function in patients who undergo parathyroidectomy for primary hyperparathyroidism by utilizing repeat neuropsychological assessment at multiple time points before and after surgery. Study Design: Prospective cohort study. Methods: A prospective study was conducted at a tertiary academic medical center between August 2014 and December 2015, including 50 patients with primary hyperparathyroidism who underwent parathyroidectomy. A panel of neurocognitive tests was administered at two separate time points: preoperative and 1‐week postoperative. Validated neuropsychological assessment tools were utilized, including Rey Auditory‐Verbal Learning Test, Trail Making Test A and B, Benton Controlled Oral Word Association, WAIS‐IV Digit Span, Hospital Anxiety and Depression Scale, Positive and Negative Affect Schedule, and Insomnia Severity Index. Barona Information Sheet was used to collect demographic data. Paired t tests were to compare pre‐ and postoperative scores. Results: Thirty‐five patients completed the preoperative and 1‐week postoperative testing. In cognitive testing, significant improvement was noted in immediate recall ( P < 0.001), working memory ( P = 0.011), and attention ( P = 0.008) at 1‐week postoperative. In mood testing, depression ( P < 0.001), anxiety ( P < 0.001), and negative affect ( P = 0.001) scores were significantly improved at 1‐week postoperative. Insomnia scores also were significantly improved at 1 week ( P < 0.001). Conclusion: Objective improvements in neurocognitive function following parathyroidectomy for primary hyperparathyroidism were noted as early as 1 week after surgery, which is earlier than previously reported. Level of Evidence: 2b. Laryngoscope, 128:775–780, 2018